2012
DOI: 10.1007/s12035-012-8370-x
|View full text |Cite
|
Sign up to set email alerts
|

The PMP22 Gene and Its Related Diseases

Abstract: Peripheral myelin protein-22 (PMP22) is primarily expressed in the compact myelin of the peripheral nervous system. Levels of PMP22 have to be tightly regulated since alterations of PMP22 levels by mutations of the PMP22 gene are responsible for >50% of all patients with inherited peripheral neuropathies, including Charcot-Marie-Tooth type-1A (CMT1A) with trisomy of PMP22, hereditary neuropathy with liability to pressure palsies (HNPP) with heterozygous deletion of PMP22, and CMT1E with point mutations of PMP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
249
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(284 citation statements)
references
References 222 publications
(324 reference statements)
3
249
0
11
Order By: Relevance
“…30 In addition, although the exact role of PMP22 is still under investigation, it has been observed that PMP22 overexpression may affect Schwann cell proliferation, differentiation, and death. 31 The correlation of ENF loss with both MC density and tactile thresholds suggests that small fiber and large fiber degeneration in CMT1A follow a parallel course.…”
Section: Statistical Analysis We Used Student T Test For Unpaired Datamentioning
confidence: 96%
“…30 In addition, although the exact role of PMP22 is still under investigation, it has been observed that PMP22 overexpression may affect Schwann cell proliferation, differentiation, and death. 31 The correlation of ENF loss with both MC density and tactile thresholds suggests that small fiber and large fiber degeneration in CMT1A follow a parallel course.…”
Section: Statistical Analysis We Used Student T Test For Unpaired Datamentioning
confidence: 96%
“…The PMP22 protein is best known for its structural role in the peripheral nervous system [Li et al, 2013]. However, a role in tumorigenesis might be concluded from the reported overexpression of PMP22 in osteosarcomas and other tumor tissues [Huhne et al, 1999;Evtimova et al, 2003;Li et al, 2005;Both et al, 2012].…”
Section: Cops3 Pmp22mentioning
confidence: 99%
“…Analogous analyses were performed for the inter-rater data. 30 were also studied. Patients with HNPP reported transient, asymmetric, focal sensory loss and weakness following mechanical stresses; conduction velocities (37.7 6 3.5 m/s) were between the values observed in CMT1A and control cohorts.…”
mentioning
confidence: 99%